The thematics of commitment : the tower & the plain - Cryle, P. M. (Peter Maxwell), 1946- (Princeton University Press, 1985)
Viewing thematic writing as the differentiation and elaboration of cultural knowledge, P.M. Cryle applies this new kind of thematics to the commitment" most often mentioned by literary critics in connection with existentialist literature. Originally published in 1985. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905